2021
DOI: 10.1021/acs.chemmater.1c02118
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fluorine in Chemomechanics of Cation-Disordered Rocksalt Cathodes

Abstract: The role of nanoscale chemomechanical behavior in macroscopic performance of functional materials is well recognized. For lithium-ion battery cathodes, tremendous effort has been devoted to the development of new chemistry and structure, yet fundamental understanding in the correlation between redox processes and mechanical properties of the novel materials lags 1 behind. In the present study, we prepare large discrete single-grains of Li-excess cationdisordered rocksalts (DRX) and investigate their chemomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Experimental work in the literature report DRX materials exposing {100} and {110} type facets, in good agreement with our computational results. Kwon 49 To elucidate the effect of surface chemistry on surface energy we employ a bootstrapping statistical method, which uses results found on a collection of smaller random samples to infer properties of the entire population, using replacement during the sampling process. For clarity, when referring to the surface, only the outermost layer of atoms is considered.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental work in the literature report DRX materials exposing {100} and {110} type facets, in good agreement with our computational results. Kwon 49 To elucidate the effect of surface chemistry on surface energy we employ a bootstrapping statistical method, which uses results found on a collection of smaller random samples to infer properties of the entire population, using replacement during the sampling process. For clarity, when referring to the surface, only the outermost layer of atoms is considered.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…show high-resolution scanning transmission electron microscope images observing a {110} type facet of the DRX material Li 1.2 Ni 0.333 Ti 0.333 Mo 0.133 O 2 . In the DRX material Li 1.3 Ti 0.3 Mn 0.4 O 1.7 F 0.3 Chen et al observed directional cracking along the ⟨100⟩ family of directions exposing {100} type planes …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, fluorination seems to affect the cracking behavior of the DRXs. Chen et al reported that the cracking of DRXs is non-directional, fluorination leads to the aligned cracking by increasing the concentration of Li on (001) plane (Chen et al, 2021b). However, it is difficult to rule out the possibility that the improved electrochemical performance is due to other effects of fluorination.…”
Section: Degradation Of Fluorinated Cationdisordered Rock-saltsmentioning
confidence: 99%
“…2 Further permutations were enabled by the substitution of O by F, a strategy with an established record in the quest for new cathode materials. 3 In disordered rocksalts, this substitution is accommodated by a lower oxidation state of the metals (M) in the initial lithiated state than in the equivalent oxide, which, coupled to the Li excess, enables the reversible utilization of M(II)/M(IV) redox couples, as in Li 2 Mn 2/3 Nb 1/3 O 2 F. 3 Further, the presence of F has been associated with improvements in long-term cycling stability, 4 linked to a greater chemical, 5 mechanical, 6 and interfacial 7 stability of the charged (oxidized) state. However, its electronic underpinnings have not been evaluated in depth.…”
Section: ■ Introductionmentioning
confidence: 99%